Optimalisasi Pemberdayaan Bagi Orang Tua Melalui Pelatihan Membaca Al-Qur’an Dengan Metode Tilawati - Zaeni, Akhmad; Maulana, Fatih Amri; Hotijah, Siti (Universitas Al-Falah As-Sunniyah Kencong Jember, 2022)
Empowerment in general can be interpreted as power, strength and ability. While the parents are the father or mother. both biological, adopted, step-in-law and in-laws. But in this study, parents are defined as people whose age has entered old age, whether they include the mother or father or not. Empowerment of parents in reading the Qur'an needs to be developed and optimized. Because the optimization of reading the Qur'an does not look at age, both children, adolescents and parents need to continue to be optimized and developed. Here we do community service with the theme